Patterns of ectoenzymatic and heterotrophic bacterial activities along a salinity gradient in a shallow tidal estuary - Cunha, M. A. (2000)
Bacterial heterotrophic communities play dominant roles in the transference of organic matter between compartments of estuarine ecosystems and, ultimately, between estuaries and the open sea. In this scenario, we investigated the responses of inflowing limnetic bacteria to the salinity gradient and the influence of these patterns on degradation and recycling of organic matter in the Ria de Aveiro. Phytoplankton biomass was maximum (0.65 to 2.10 mg C l–1) in the mid- or inner-estuary and declined sharply at about 30 psu. Bacterial communities reached highest densities in the midand inner-sections of the estuary (up to 15.3 × 109 cell l–1), being 2 to 3 times higher than in the outerestuary during identical tidal conditions. The rates of ectoenzymatic hydrolysis were also maximum in the mid-estuary or the inner-section. Values ranged from 4.3 to 181.3 nmol l–1 h–1 for β-glucosidase and from 490 to 5374 nmol l–1 h–1 for leu-aminopeptidase. At the transition from the limnetic environment to the main body of the lagoon an exceptional increase in the utilisation of carbohydrate was observed (β-glucosidase activity). This was accompanied by major increases in glucose incorporation, with maximum values of 17.7 nmol l–1 h–1. Turnover rate ranged from 0.3 to 4.1% h–1 in the outer estuarine section increasing to maximum values in the inner section (10.4 to 39.4% h–1). Statistical analysis revealed that the variation in ectoenzymatic activities could be significantly related to bacterial abundance, which in turn, was highly associated with variations in salinity, temperature and chlorophyll a. Within the salinity gradient, the profiles of bacterial abundance, glucose uptake and ectoenzymatic activity generally agreed with a curvilinear pattern, with a peak at ~25 to 30 psu. Ectoenzymatic activity showed fairly conservative behaviour during tidal transport along the salinity gradient compared to the more reactive parameters of glucose metabolism.